A method to select IT service management processes for improvement - Shrestha, Anu; Cater-Steel, A.; Toleman, M.; Tan, Wui-Gee (2014)
Although process improvement is crucial for organizations that seek quality in their operations, there is a lack of explicit guidance on how to select the critical pro cesses to improve. We propose a structured method to guide the selection of processes for improvement in IT service management (ITSM) and designed and evaluated a decision support system (DSS) for process selection. We designed the process selection method to be theoretically grounded, have balanced business and ITSM objective s, and be supported by a DSS. We took a design science research approach to develop, demonstrate, and evaluate the process selection method and DSS. We applied task- technology fit to inform the design and explain the DSS’s development and utility. We used the balance d scorecard and SERVQUAL models to structure business objective s and service gap perceptions. We conducted ex ante evaluation during the development process and inter views for an ex post qualitative evaluation. The results suggest the method is effective, valid, and useful and that it offers benefits in terms of perceived decision quality and decision efficiency. The DSS’s utility was confirmed because it enabled evidence-based decision support for the process selection method. Using the proposed method, practitioners can follow a workflow for selecting critical IT service processes that need to be improved based on current business objectives and confirmed by key process stakeholders. The proposed method and the DSS proto type could form a basis for future research in defining the scope for process improvement projects in other fields.